PENDIDIKAN KEWARGANEGARAAN DALAM PERSPEKTIF FILSAFAT ILMU - Muhammad Malik Purnama,; Muhammad Nurwahidin,; Sudjarwo, Sudjarwo (Jurnal Cakrawala Ilmiah, 2022)
The goal of Indonesian education is to make people who are religious, insightful, have noble character, and are capable. In order to achieve the nation's noble values, it is necessary to practice learning and applying citizenship education. This research technique uses a literature review study. References for this writing come from related articles, papers, to books. This article provides a philosophical perspective on civic education. Philosophy of science itself has 3 foundations, including Epistemology, Ontology, and Axiology. Scientific citizenship education can be a solution in achieving this. Citizenship education basically talks about values, morals, normals, and ethics that apply in everyday life. Citizenship education in its application is a subject that must be applied from the low level to the high level due to the importance of being an intelligent and character citizen through citizenship education.